2024
DOI: 10.1038/s41597-024-03210-6
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics and genetic analysis of solvent-producing Clostridium species

Rasmus O. Jensen,
Frederik Schulz,
Simon Roux
et al.

Abstract: The genus Clostridium is a large and diverse group within the Bacillota (formerly Firmicutes), whose members can encode useful complex traits such as solvent production, gas-fermentation, and lignocellulose breakdown. We describe 270 genome sequences of solventogenic clostridia from a comprehensive industrial strain collection assembled by Professor David Jones that includes 194 C. beijerinckii, 57 C. saccharobutylicum, 4 C. saccharoperbutylacetonicum, 5 C. butyricum, 7 C. acetobutylicum, and 3 C. tetanomorphu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…A joint LanzaTech-JGI project has added another 270 genomes from the DJ culture collection. Of these, 72% were C. beijerinckii genomes, consisting of 160 genomes from the NCP industrial strain collection and 34 genomes of strains originating from the international culture collection [2,38]. The phylogenetic analysis from the expanded number of genome sequences confirmed that the C. beijerinckii species consists of four distinct subgroups that possibly can be considered as subspecies.…”
Section: The Diversity Within C Beijerinckii Speciesmentioning
confidence: 89%
See 4 more Smart Citations
“…A joint LanzaTech-JGI project has added another 270 genomes from the DJ culture collection. Of these, 72% were C. beijerinckii genomes, consisting of 160 genomes from the NCP industrial strain collection and 34 genomes of strains originating from the international culture collection [2,38]. The phylogenetic analysis from the expanded number of genome sequences confirmed that the C. beijerinckii species consists of four distinct subgroups that possibly can be considered as subspecies.…”
Section: The Diversity Within C Beijerinckii Speciesmentioning
confidence: 89%
“…The three species are closely related phylogenetically and belong together in a separate phylogenetic clade. The members of the species in this clade encode the sol operon in the gene order ald-ctfA-ctfB-adc and lack a pdc gene [38]. As a general observation, all three species appear to perform more effectively on plant-based substrates such as molasses than they do on maize or laboratory media with glucose and/or sucrose as the sole energy source.…”
Section: The Industrial Saccharolytic Solvent-producing Speciesmentioning
confidence: 94%
See 3 more Smart Citations